2020
DOI: 10.1371/journal.pone.0241830
|View full text |Cite
|
Sign up to set email alerts
|

Intervention through Short Messaging System (SMS) and phone call alerts reduced HbA1C levels in ~47% type-2 diabetics–results of a pilot study

Abstract: Purpose Despite extensive research and newer methods of interventions, the incidence and prevalence of diabetes is increasing at an alarming rate. Currently, according to world health organization (WHO) statistics, 422 million individuals are suffering from diabetes worldwide. In India, recent estimates have reported a significant increase in the number of diabetics in the last decade. Poor dietary habits, minimal adherence to treatment regimens, lack of timely education are some of the contributing factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…18 Another study revealed that providing care and support with a mobile phone for 8 months improved clinically relevant diabetes-related health outcomes by increasing knowledge and self-efficacy for selfmanagement behaviors. 19 Another important thing to consider when conducting coaching is to shorten the session and lengthen the duration of each session. 20 By using a mobile phone, Android Application-Based Health Coaching automatically motivates individuals to adopt a healthy lifestyle by predicting health risk early, providing personal recommendation, and evaluating personal goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study revealed that providing care and support with a mobile phone for 8 months improved clinically relevant diabetes-related health outcomes by increasing knowledge and self-efficacy for selfmanagement behaviors. 19 Another important thing to consider when conducting coaching is to shorten the session and lengthen the duration of each session. 20 By using a mobile phone, Android Application-Based Health Coaching automatically motivates individuals to adopt a healthy lifestyle by predicting health risk early, providing personal recommendation, and evaluating personal goals.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Another study revealed that providing care and support with a mobile phone for 8 months improved clinically relevant diabetes-related health outcomes by increasing knowledge and self-efficacy for self-management behaviors. 19 Another important thing to consider when conducting coaching is to shorten the session and lengthen the duration of each session. 20 …”
Section: Discussionmentioning
confidence: 99%